Oral manifestations in patients with Diabetes mellitus (Research, Society and Development, 2022)
The term “Diabetes mellitus” is used to identify a group of disorders characterized by elevated blood glucose levels. This elevation is the result of a deficiency in insulin secretion or an increase in cellular resistance to the actions of insulin, leading to a variety of metabolic abnormalities involving carbohydrates, fats, and proteins. Given the above, this study aimed to review the literature on local anesthetics used in dentistry, highlighting necessary information regarding the choice and amount of anesthetic, preventing the occurrence of complications. For the construction of this work, a bibliographic survey was carried out in the databases SciVerse Scopus, Scientific Electronic Library Online (Scielo), U.S. National Library of Medicine (PUBMED) and ScienceDirect, using the Mendeley reference manager. The main oral manifestations and complications related to Diabetes Mellitus involve xerostomia, dysgeusia, oral infections, dental caries and periodontal diseases. There are also reports of lesions in the oral mucosa, such as stomatitis, geographic tongue, benign migratory glossitis, fissured tongue, traumatic ulcer, lichen planus, oral lichenoid reaction and angular cheilitis. The prevalence and susceptibility of developing these lesions is higher in patients with DM compared to controls. Diabetes Mellitus is a chronic, non-communicable and endemic disease, which results in multiple complications, which increase when the patient's glycemic control is inadequate. Thus, physicians and dentists must be aware of the various oral manifestations of diabetes to make an early diagnosis.